Eqivalent Intergranular Void Ratio Analysis Of Sand-Silt Mixtures - Oktaviana, Ida Sri (Jurusan Teknik Sipil Universitas Tadulako, 2012)
In the recent last decade studies indicated that the void ratio only might not be good to characterize the sand with fines state variable and fine grains in fact were contributed to the intergrain contact. Contribution of fine content defined in the intergranular (es) and interfine (ef) void ratio studied by Thevanayagam (1998). Moreover, ThevanayagamÂ (2000) introduced equivalent intergranular void ratio (es)eq and equivalent interfine void ratio (ef)eq, as contact index which include the contribution of fine contents as an active intergrain contact (b). In this article, the void ratio given in the 6 sand-silt mixture from past researches recalculated to intergranular void ratio and equivalent intergranular void ratio for FC < FCth using estimated b value obtained from the line equation from chart given by Thevanayagam (2010). The new chart replottedÂ and compared to the one given in those articles. The results shows that for most sand-silt mixture using es and (es)eq rather than e as the indices to characterize the contribution of fine grains in a soil mix for FC< FCth indicated good results that shows in plotted data points of soil mixtures that located close to a single line compare to the one using void ratio (e) only. The line equation proposed by Thevanayagam (2010) can be used to estimate the b value to obtain the equivalent intergranular void ratio